Epistemología de la política educativa y justicia social en América Latina - Tello, César (Nómadas. Critical Journal of Social and Juridical Science, 2011)
This paper is the reflection of a study that I have been developing the category of educational policy epistemologies, from three topics: epistemology of the oppressed, the interdisciplinary and strange reality that cross as potential reality to think that Latin America and hindering the epistemological perspective of educational policy and social justice in Latin America. Well our concern in the inquiry that we made and presented in this paper is to highlight the importance of epistemological positions as political posturing, and as ethical positions in front of the regional reality. To understand, finally, as displayed from various perspectives, not always explicit, research on education policy in Latin America. Conceptually intertwined topics under the category of anthropology ethic Edgar Morin and the prospect of social justice. Without a thorough examination of the latter category, but taking it as a goal for the transformation.
Keywords: educational policy; epistemology; latin american reality